Raisins and Oral Health. Issue 1 (21st June 2013) - Wong, Allen; Young, Douglas A.; Emmanouil, Dimitris E.; Wong, Lynne M.; Waters, Ashley R.; Booth, Mark T.
Abstract Traditionally, raisins have been thought to promote dental caries due to their suspected "stickiness" and sugar content. Current research identifies some evidence contrary to traditional thought, suggesting that raisins may not contribute to dental caries. This article reviews new findings with regards to raisins and the 3 conditions that are thought to contribute to the formation of dental caries; low oral pH, adherence of food to teeth, and biofilm (bacterial) behavior. The studies reviewed concluded that raisin: consumption alone does not drop oral pH below the threshold that contributes to enamel dissolution, do not remain on the teeth longer than other foods, and contain a variety of antioxidants that inhibit Streptococcus Mutans, bacteria that is a primary cause of dental caries. Further research in this area should be considered.